Removal and Recovery of Toxic Silver Ion Using Deep-Sea Bacterial Generated Biogenic Manganese Oxides - Pei, Yuanjun (Public Library of Science, 2013)
Products containing silver ion (Ag(+)) are widely used, leading to a large amount of Ag(+)-containing waste. The deep-sea manganese-oxidizing bacterium Marinobacter sp. MnI7-9 efficiently oxidizes Mn(2+) to generate biogenic Mn oxide (BMO). The potential of BMO for recovering metal ions by adsorption has been investigated for some ions but not for Ag(+). The main aim of this study was to develop effective methods for adsorbing and recovering Ag using BMO produced by Marinobacter sp. MnI7-9. In addition, the adsorption mechanism was determined using X-ray photoelectron spectroscopy analysis, specific surface area analysis, adsorption kinetics and thermodynamics. The results showed that BMO had a higher adsorption capacity for Ag(+) compared to the chemical synthesized MnO(2) (CMO). The isothermal absorption curves of BMO and CMO both fit the Langmuir model well and the maximum adsorption capacities at 28°C were 8.097 mmol/g and 0.787 mmol/g, for BMO and CMO, respectively. The change in enthalpy (ΔH(θ)) for BMO was 59.69 kJ/mol indicating that it acts primarily by chemical adsorption. The change in free energy (ΔG(θ)) for BMO was negative, which suggests that the adsorption occurs spontaneously. Ag(+) adsorption by BMO was driven by entropy based on the positive ΔS(θ) values. The Ag(+) adsorption kinetics by BMO fit the pseudo-second order model and the apparent activation energy of E(a) is 21.72 kJ/mol. X-ray photoelectron spectroscopy analysis showed that 15.29% Ag(+) adsorbed by BMO was transferred to Ag(0) and meant that redox reaction had happened during the adsorption. Desorption using nitric acid and Na(2)S completely recovered the Ag. The results show that BMO produced by strain MnI7-9 has potential for bioremediation and reutilization of Ag(+)-containing waste.